Type curve analysis of superheated steam flow in offshore horizontal wells. (October 2017) - Sun, Fengrui; Yao, Yuedong; Li, Xiangfang; Zhao, Lin
Highlights: Wellbore modeling becomes a hot spot in the thermal recovery engineering. A model is proposed to analyze the flow and heat transfer characteristics of SHS in offshore horizontal wells. Type curves of SHS flow in offshore horizontal wells are obtained by iteration method. The effect of injection parameters on superheat degree are studied in detail. The effect of turbulent flow of seawater on superheat degree are studied in detail. Abstract: In order to estimate the distributions of temperature and pressure of superheated steam (SHS) in offshore horizontal wells, a series of theoretical studies are conducted. Based upon the mass, energy and momentum conservation equations in wellbores, and heat transfer models in seawater and formation, a mathematical model is established. Numerical method is then adopted to solve the model. The distributions of temperature and pressure are obtained by finite difference method on space under the controlling of iteration accuracy. The predicted results are compared against field data, which shows the maximum relative errors for temperature and pressure are 0.76% and 4.21%, respectively. Some main findings from the model show that: (1). Superheat degree along the horizontal section of the wellbore increases with increasing of injection rate at platform; (2). Superheat degree increases with increasing of injection temperature at platform; (3). Superheat degree decreases with increasing of injection pressure at platform; (4). The flow of seawater can obviously reduce the superheat degree in wellbores.